Knowledge, attitude, and practice regarding molar-incisor hypomineralization among postgraduates and faculty members of K.M. Shah Dental College and Hospital, Vadodara, Gujarat, India - Kritika K Daryani; K S Poonacha; Anshula N Deshpande; Bhavna H Dave; Monika Khoja; Kinjal S Patel (Wolters Kluwer Medknow Publications, 2019)
Context: Molar-incisor hypomineralization (MIH) is a defect existing in the form of demarcated and opaque lesions and in severe cases with posteruptive enamel breakdown. There is a lack of knowledge, learning, and practice on MIH in pediatric dentistry. Aims: This study aimed to identify the knowledge, attitude, and practice on MIH among postgraduates and faculty members of K.M. Shah Dental College and Hospital, Vadodara, Gujarat, India. Settings and Design: A questionnaire-based study was conducted among the dental staff and postgraduate students of K.M. Shah Dental College. Subjects and Methods: The questionnaire was hand-delivered to all 142 participants, and they were asked to fill it within 5 working days. The questionnaire included demographic information, prevalence, incidence, and severity of MIH in Vadodara City. Statistical Analysis Used: Data analysis was done using SPSS version 20.0 (SPSS Inc., Chicago, IL, USA). The data were found to be normal by the Kolmogorov-Smirnov test. Intergroup comparison was done using the Chi-square test for proportions and percentages (qualitative data). Results: 43.3% of the respondents could not implement the clinical criteria to diagnose MIH, 92.5% of the respondents recommended to include MIH-associated case studies in the curriculum, 95% of the respondents recommended to conduct awareness programs, and 40.5% of the respondents indicated a lack of knowledge as a barrier for performing MIH management. Conclusions: There is a need for dentists to attend continuing dental education programs and various awareness programs on MIH and to introduce in-depth information on MIH-etiology and its treatment into the dental curriculum.